Plant–soil negative feedback explains vegetation dynamics and patterns at multiple scales - Vincenot, Christian E.; CARTENI', FABRIZIO; BONANOMI, GIULIANO; MAZZOLENI, STEFANO; GIANNINO, FRANCESCO (Oikos, 2017)
Spatial patterns and self-organization of plants has been a subject of fascination because the underlying mechanisms have been hard to determine, raising different explanatory hypotheses. Plant–soil negative feedback (PSNF) – defined as the induction of negative conditions for conspecific establishment – has been widely studied in both field and laboratory conditions, and conceptually demonstrated by some modelling works. We present a mechanistic model, integrating individual plants inside an agent-based framework, to explore the effects of PSNF on the spatial and temporal dynamics of virtual populations and communities of plants of diverse growth forms. This endeavour led to the reproduction of well-known vegetation patterns observed at various scales, demonstrating for the first time a unified mechanism behind the spatial patterns of Janzen–Connell seedlings’ distribution, ring formation, and the high species mobility in species-rich grasslands. These results support the ecological relevance of PSNF in the regulation of spatial organization and biodiversity dynamics in plant communities. More specifically, PSNF due to autoxicity seems most coherent with the spatio-temporal scale of dynamics displayed here.